Ship to Ship (STS) Transfer οf Cargo: Latest Developments and Operational Risk Assessment - Ventikos, Nikolaos P.; Stavrou, Dimitrios I. (SPOUDAI Journal of Economics and Business, 2013)
The significant development of Ship to Ship (STS) transfer of cargo operations originates from different operational and trading reasons and factors, all of which however in the context of optimizing the distribution plan between the source and the final consumers (markets). The transferred cargo can be either petroleum products, or liquefied gases (LPG, LNG), or even some dry bulk cargoes. The IMO resolution, MEPC 186(59)/2009, gives to tanker vessels the full operational responsibility of an STS operation of petroleum products. To reduce the possibility of a potential accident with severe effects, risk assessment is necessary for the evaluation of the hazards embedded in the procedures and to prevent the occurrence of mishaps during STS transfers by taking additional control measures. The aim of this paper is to describe the latest developments related to STS transfer cargo procedures and moreover to scrutinize on the implementation of risk assessment in the context of optimizing the procedures. It is intended to determine the factors that can affect the operations; accidents that happened in the past are presented in order to investigate the parameters that should be considered as lessons learned to avoid similar unpleasant situations in future activities related to STS operations. JEL Classification: R41; P41; Q51.